Pengaruh Edukasi Audio Visual terhadap Pengetahuan Ibu dalam Penanganan Anak Temper Tantrum Usia Prasekolah di Tk Desa Kepoh Kecamatan Kepohbaru Kabupaten Bojonegoro - Fitria Asmorosari; Nesti Nur Asikhin; Dadang Kusbiantoro; Sylvi Harmiardillah (Inovasi Kesehatan Global, 2024)
. Children with temper tantrums will show reactions that are out of the child's control such as screaming, rolling and screaming so that the impact of the child's intellectual and social development is not balanced and the child uses the tantrum as a weapon so that his desires are fulfilled. The lack of knowledge of mothers in dealing with temper tantrums has a bad impact on children, so knowledge about handling temper tantrums is needed. Education using audiovisual is effective in increasing knowledge because it is interesting, not boring, and easy to carry around. The purpose of the study was to determine the influence of audiovisual education on maternal behavior in the handling of preschool-age temper tantrums. The design of this study uses a Pre-Experimental One Group Pretest-Posttest conducted on 34 mothers taken using the Total Sampling technique in May 2023. The intervention provided was in the form of playing educational videos on handling temper tantrums. The research data was taken with a temper tantrum knowledge questionnaire, then analyzed using the Paired T-test. The results showed that there was a significant influence on the knowledge of mothers about the treatment of temper tantrums after being given the audio-visual education method (p=0.000). Audio-visual education can increase a person's knowledge because the material conveyed can be received through the senses of sight and hearing. It is recommended that the public can enrich information about the treatment of temper tantrums, and for researchers to further research other aspects or use different methods.